2007
DOI: 10.1128/jvi.02090-06
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Feline Immunodeficiency Virus in Feral and Companion Domestic Cats of New Zealand

Abstract: Nested PCR was used to amplify envelope V3-V6 gene fragments of feline immunodeficiency virus (FIV) from New Zealand cats. Phylogenetic analyses established that subtypes A and C predominate among New Zealand cats, with clear evidence of intersubtype recombination. In addition, 17 sequences were identified that were distinct from all known FIV clades, and we tentatively suggest these belong to a novel subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
4
37
1
Order By: Relevance
“…However, using molecular methods, this prevalence decreases to 4 to 2% of the worldwide cat population (Hayward et al, 2007). This variation is due to population density, reproductive status, age, gender and living conditions, in particular the frequency of street visitation and reproductive disputes (Norris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, using molecular methods, this prevalence decreases to 4 to 2% of the worldwide cat population (Hayward et al, 2007). This variation is due to population density, reproductive status, age, gender and living conditions, in particular the frequency of street visitation and reproductive disputes (Norris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recombination may modify viral properties and aid adaptation to new host species. This applies also to RNA viruses infecting cats and dogs; for example, group 1 feline and canine coronaviruses [8,21], feline calicivirus [4], feline immunodeficiency virus [2,7,10,29], and canine distemper virus [6]. Recently Shackelton et al [31] found some evidence of natural recombination among porcine, mink, and rodent parvoviruses by analyzing the genetic data deposited in databases, and discussed the possibility that recombination may be important in the natural evolution of parvoviruses, especially in circumstances where parvoviruses cause persistent infections.…”
mentioning
confidence: 99%
“…The retrovirus, FIV, a close relative of HIV, has been identified in domestic cats (Felis catus) in New Zealand (Swinney et al 1989;Hayward et al 2007). Phylogenetic tree construction of envelope (env) gene sequences has shown that two of the five possible FIV subtypes are found in New Zealand infected cats (Hayward et al 2007).…”
Section: Ib Viral Hybridisationmentioning
confidence: 99%
“…Phylogenetic tree construction of envelope (env) gene sequences has shown that two of the five possible FIV subtypes are found in New Zealand infected cats (Hayward et al 2007). These two subtypes, A and C, co-occur in cat populations, leading to dual infection and consequently recombination/ hybridisation.…”
Section: Ib Viral Hybridisationmentioning
confidence: 99%